Futurist Performance : Theory and practice in the drama, scenography, acting, costumes, film and music of the Italian Futurists - Kirby, Michael (New York : E.P. Dutton & Co, Inc., 1971)
The art movement known as Futurism began in 1909 with the publication of the Foundation and Manifesto of Futurism by Filippo Tommaso Marinetti. Although the work of the Italian Futurist painters and sculptors is widely known and their contribution generally understood, Futurist developments in the performance arts, many of them created by the same painters and sculptors, are almost completely unknown in this country. This book attempts to survey these developments in a systematic way and to explain their importance. It covers Futurist work in the fields of drama, scenography, acting, dance, music, cinema, and radio, and it concerns itself both with actual performance and with performance theory, which was elucidated primarily in a series of manifestos. The earliest Futurist performances took the form of Serate, or Evenings, at which both poetry and polemics were read. The outstanding characteristic of these serate was a noisy, direct, and sometimes riotous audience-performance relationship ; later presentations, spatially intermixed the performance and audience. The most important Futurist plays, called Sintesi, were very short and non-naturalistic, and they ranged in style from Symbolist and didactic to alogical and nonrepresentational. In them can be found the origins of Dada, Surrealism, and the Theatre of the Absurd ; they influenced both Luigi Pirandello and Thornton Wilder. Other fascinating aspects of Futurist performance included : their theories of kinetic scenery ; Giacomo Balla's actorless performance of 1917 where Orchestrated lights changed in time to Stravinsky's music ; Luigi Russolo's new theories of music outlined in his The Art of Noise and other writings, in which he accepted any and all sounds as potential for music ; the 1916 Futurist film Vita Futurista and the manifesto Futurist Cinematography that anticipated many of the concepts of later avant-garde films. Futurist Performance shows clearly how in its rejection of traditional forms, i
Appia, Adolphe ; Artaud, Antonin ; Azari, Fedele ; Bakst, Leon ; Ball, Hugo ; Balla, Giacomo ; Belloli, Carlo ; Boccioni, Umberto ; Breton, André ; Burljuk, David ; Buzzi, Paolo ; Cage, John ; Cangiullo, Francesco ; Carducci, Giosuè ; Carli, Mario ; Carrà, Carlo ; Chiti, Remo ; Cocteau, Jean ; Corra, Bruno ; Corradini, Arnaldo ; Craig, Edward Gordon ; Depero, Fortunato ; Dessy, Mario ; Fillia ; Ginna, Arnaldo ; Jannelli, Guglielmo ; Marinetti, Filippo Tommaso ; Mauro, Augusto ; Montalti, Mauro ; Nicastro, Luciano ; Prampolini, Enrico ; Pratella, Francesco Balilla ; Rognoni, Angelo ; Russolo, Luigi ; Scaparro, Mario ; Settimelli, Emilio ; Scaparro, Mario ; Steiner, Giuseppe ; Volt
Selected Bibliography p. 322-327
Selected Chronology of Futurist Performance p. 319-321
Engels
boek
Keywords: Italië